Case Definitions of Clinical Malaria under Different Transmission Conditions in Kilifi District, Kenya - Mwangi, Tabitha W. (2005)
BACKGROUND: Clear case definitions of malaria are an essential means of evaluating the effectiveness of present and proposed interventions in malaria. The clinical signs of malaria are nonspecific, and parasitemia accompanied by a fever may not be sufficient to define an episode of clinical malaria in endemic areas. We defined and quantified cases of malaria in people of different age groups from 2 areas with different rates of transmission of malaria. METHODS: A total of 1602 people were followed up weekly for 2 years, and all the cases of fever accompanied by parasitemia were identified. Logistic regression methods were used to derive case definitions of malaria. RESULTS: Two case definitions of malaria were derived: 1 for children 1–14 years old and 1 for infants (<1 year old) and older children and adults (≥15 years old). We also found a higher number of episodes of clinical malaria per person per year in people from an area of low transmission of malaria, compared with the number of episodes in those from an area of higher transmission (0.84 vs. 0.55 episodes/person/year; incidence rate ratio, 0.66 [95% confidence interval, 0.61–0.72]; P < .001). CONCLUSIONS: Case definitions of malaria are bound to be altered by factors that affect immunity, such as age and transmission. Case definitions may, however, be affected by other immunity-altering factors, such as HIV and vaccination status, and this needs to be borne in mind during vaccine trials.